Why the Norwegian shareholder income tax is neutral - Jan Södersten (Uppsala University, Department of Economics, 2019)
This note extends the work by Sørensen (2005) and others by demonstrating why the Norwegian Shareholder Income Tax may be neutral between the two sources of equity funds, i.e. new share issues and retained earnings, despite the fact that the retention of earnings to finance new investment does not add to the tax benefits. The analysis crucially relies on the assumption that the deduction for the imputed rate of return is capitalized into the market prices of corporate shares. Absent capitalization, the shareholder tax is rather likely to leave the distortions caused by the double taxation of corporate source income unaffected.
urn:nbn:se:uu:diva-375434
Keywords: H24; H25; H32; 330; Corporate and shareholder taxation; tax neutrality; cost of capital